Factors for Decision to C-section Delivery in Indonesia: Insights from IDHS 2017 - Diki Septian; Nurhalina Sari; Wayan Aryawati (Jurnal Bidan Cerdas, 2023)
Introduction: Cesarean delivery (C-sections) showed 17.6% of all deliveries in Indonesia, which exceeded the WHO standard of 15%. C-sections in government hospitals reached 20-25%; in private hospitals, the number was higher, above 30%. Purpose: The study aimed to determine the factors influencing the decision of cesarean section delivery in Indonesia. Method: The study used a cross-sectional design. Data came from the Indonesian Health Demographic Survey (IDHS) 2017. The population and samples were 2,464 women aged 15-49 years—data analysis using chi-square test and multiple logistic regression. Result: The study found that the proportion of cesarean delivery in private hospitals reached 53.8%. Factors related to the decision to c-section delivery (p<0.05) were maternal education, place of residence, domicile island, spouse's occupation and education, wealth index, health insurance, and antenatal care history. Conclusion: The wealth index was the dominant factor for the decision to c-section delivery. The government is expected to be able to improve the quality of services and facilities in cesarean section delivery by government hospitals so that it can be the alternative decision for the community with a variety of wealth index and education backgrounds.